Evaluating the effect of routine hoof trimming on fore and hind hooves impact phase kinetics - Faramarzi, B.; Nelson, S.; Dong, F. (Journal of Equine Veterinary Science, 2022)
Imbalances and altered kinetics of the hoof result in lameness in horses. Previously, studies have focused on the midstance phase of a gait, hence, available information on the impact phase is scarce. This study aimed to investigate the effect of hoof trimming on the fore and hindhooves at the impact phase of the walk. Our objective was to compare the kinetic variables of force (N), contact area (cm2), contact pressure (kPa), and peak contact pressure (kPa) before and after hoof trimming. Nine Arabian horses were walked straight over a pressure plate to collect the above kinetic variables for both left and right fore and hindhooves. The impact phase was defined as the first contact of each hoof with the pressure plate, which was collected as the first frame of data. The signed rank test was used to determine the difference of each kinetic variable between pre and post trimming for each hoof. A statistical P-value <.05 was considered significant. Routine hoof trimming of the forehooves did not significantly change the hoof kinetic variables, except for an increase of 56% (P = .0391) for contact area (CA) after trimming of the right forehooves. For the left hindhooves, force increased by 35% (P = .019) and CA increased by 18% (P = .039) after trimming. The data revealed how hoof trimming may affect hoof kinetics at the impact phase of the walk for this group of horses and demonstrates the need for further research in other breeds and disciplines.